2011
DOI: 10.1159/000328909
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy in the Arab Gulf Countries

Abstract: While the prevalence of diabetes mellitus is increasing worldwide, one third of the diabetic patients will eventually develop chronic kidney disease. The aim of this review is to present the available data on diabetic nephropathy and its complications in the Arab Gulf countries. This will eventually help to raise the awareness of both government and healthcare systems towards the substantial value of prevention, early detection as well as proper management of both diabetes mellitus and chronic kidney disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Several studies have reported a higher prevalence of microvascular damage (retinopathy and kidney disease) in hypertensive women [31,32], but no data have been published showing a higher prevalence of microvascular damage in women with type 2 diabetes. A recent retrospective study showed that DN appeared significantly earlier among males than females [33]. This finding may explain the gender difference we found in our cross-sectional study based on a single observation.…”
Section: Discussionmentioning
confidence: 48%
“…Several studies have reported a higher prevalence of microvascular damage (retinopathy and kidney disease) in hypertensive women [31,32], but no data have been published showing a higher prevalence of microvascular damage in women with type 2 diabetes. A recent retrospective study showed that DN appeared significantly earlier among males than females [33]. This finding may explain the gender difference we found in our cross-sectional study based on a single observation.…”
Section: Discussionmentioning
confidence: 48%
“…At present, ~7% of Chinese adults are DM patients, as many as 0.92 billion 35. Among patients who have had diabetes for a period of 10–20 years, approximately one-third will develop DN 36. The prevalence rate of DN in our country is increasing, and middle-aged and elderly people account for a large portion, with the patient group having a tendency to become younger.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons include increasing urbanisation, aging of the population, increasing obesity and falling levels of physical activity [31,32]. Efforts to reduce the burden of ESKD in Libya should therefore focus on measures to reduce incidence of type 2 diabetes mellitus [33,34] through public awareness, screening and promotion of a healthy lifestyle as well as prevention of microvascular complications in those with diabetes [35]. Glomerulonephritis was the second most frequent cause of ESKD in Libya in prevalent and incident cases and was significantly more common among young and male patients.…”
Section: Discussionmentioning
confidence: 99%